Analisis Penerapan Definisi Pasar Bersangkutan dalam Hukum Persaingan Usaha atas Penggabungan Digital (Digital Merger) di Indonesia - Claudia Angelica Simanjuntak; Kukuh Tejomurti (Indonesian Journal of Social Sciences and Humanities, 2026)
The rapid growth of Indonesia’s digital economy has intensified merger activities among digital platform companies. However, the existing competition law framework, particularly the relevant market definition under Law Number 5 of 1999, remains grounded in product and geographic dimensions developed for conventional markets. This study aims to analyze the application of a uniform relevant market definition in assessing digital mergers and to examine its relevance within the development of the digital economy. Using normative legal research with statutory and conceptual approaches, this study examines the GoTo (Gojek–Tokopedia) merger as an illustrative case. The findings indicate that the application of a uniform definition has not fully reflected digital market power arising from network effects, data control, and ecosystem integration. The study further outlines adjustments through an ecosystem-based conceptual approach that may be implemented through KPPU regulatory instruments, as well as normative refinements including the expansion of Article 1(10), the introduction of qualitative notification criteria, and the incorporation of gatekeeper position as an assessment parameter.